Equivalent relations, context and cotext in bilingual dictionaries - Gouws, Rufus H. (HERMES - Journal of Language and Communication in Business, 2002)
Users of bilingual dictionaries often have problems to choose the correct translation equivalent for a given occurrence of the source language form. This could be due to a lack of entries indicating the relevant context and cotext of the translation equivalents. This paper deals with different types of equivalent relations in bilingual dictionaries and the varying need for entries to support the translation equivalents. It is argued that where a relation of semantic divergence prevails the inclusion of context and cotext entries are of extreme importance. The function of a dictionary should determine the nature and extent of the supporting entries. Lexicographers should be well aware of the additional need for context and cotext entries in the treatment of synsemantic words. Consequently they have to negotiate the problems resulting from under addressing, over addressing and zero addressing. It is suggested that procedures of addressing equivalence can help to ensure equivalent discrimination.